2015
DOI: 10.1001/jamadermatol.2015.2230
|View full text |Cite
|
Sign up to set email alerts
|

Genetic vs Environmental Factors That Correlate With Rosacea

Abstract: IMPORTANCE To our knowledge, this is the first study on rosacea to formally define genetic and environmental contributions. OBJECTIVES To study a cohort of identical and fraternal twins to determine whether genetic factors contribute to rosacea development and, if genetic factors are present, quantitatively estimate the genetic contribution, as well as to identify environmental factors that correlate with rosacea by controlling for genetic susceptibility. DESIGN, SETTING, AND PARTICIPANTS Identical and frater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(71 citation statements)
references
References 16 publications
2
65
0
4
Order By: Relevance
“…The genetics of rosacea are poorly understood. A study in twins suggests a 46% genetic contribution; furthermore, a genomewide association study confirmed that three human leucocyte antigen (HLA) alleles and a small nucleotide polymorphism are genetically linked to rosacea . Interestingly, rosacea‐associated HLA genes have also been identified in other disorders with inflammatory, neural, granulomatous and ocular manifestations …”
Section: Phenotypes Of Rosaceamentioning
confidence: 99%
“…The genetics of rosacea are poorly understood. A study in twins suggests a 46% genetic contribution; furthermore, a genomewide association study confirmed that three human leucocyte antigen (HLA) alleles and a small nucleotide polymorphism are genetically linked to rosacea . Interestingly, rosacea‐associated HLA genes have also been identified in other disorders with inflammatory, neural, granulomatous and ocular manifestations …”
Section: Phenotypes Of Rosaceamentioning
confidence: 99%
“…[1] Previous studies have implicated microbial colonization and the cognate immune response as the critical driver of rosacea. [2,3] Increased levels of Demodex mites and associated bacteria (bacillus), antimicrobial peptides (eg cathelicidin/LL37), host immune variables (eg Tolllike receptor (TLR)-2) and nutrients (eg vitamin D3) are reported to alter the innate immune response and cause chronic inflammation and the facial skin sensitivity in rosacea.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…One of the most important extrinsic ageing factors is sunlight, particularly exposure to ultraviolet (UV) B irradiation, which is a major cause of skin photoageing. [1,2] Exposure of keratinocytes to UVB radiation activates various cytokines such as tumor necrosis factor-α (TNF-α), interleukin-1α…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…The association between rosacea and BMI was significant, and weight gain with age and central obesity increased the risk of rosacea . Likewise, a twin study exhibited a positive correlation between rosacea and BMI, ultraviolet radiation exposure and cardiovascular morbidity . Although there were conflicting results among clinical studies, obesity per se may be relevant to rosacea on the basis of a common pathogenesis involving chronic inflammation .…”
Section: Discussionmentioning
confidence: 99%